Shear-Wave Dispersion Slope from US Shear-Wave Elastography: Detection of Allograft Damage after Liver Transplantation - Lee, Dong Ho; Lee, Jae Young; Bae, Jae Seok; Yi, Nam-Joon; Lee, Kwang-Woong; Suh, Kyung-Suk; Kim, Haeryoung; Lee, Kyung Bun; Han, Joon Koo (Radiology, 2019)
Background Allograft damage (hepatic parenchymal damage) after liver transplant is associated with the degree of necroinflammation in graft liver. According to a recent animal study, shear-wave dispersion slope obtained at US shear-wave elastography (SWE) is associated with necroinflammatory activity in the liver. Purpose To evaluate the role of shear-wave dispersion slope in detecting allograft damage after liver transplant. Materials and Methods In this prospective study, 104 liver transplant recipients underwent percutaneous liver biopsy for allograft evaluation from December 2017 to November 2018. All participants underwent allograft SWE examination just before liver biopsy, and liver stiffness and shear-wave dispersion slope were obtained. Allograft damage was diagnosed by histopathologic analysis. Clinical and imaging factors related to liver stiffness and shear-wave dispersion slope were determined by multivariable linear regression analysis. Diagnostic performance of each variable in detecting allograft damage was evaluated by comparing area under the receiver operating curve (AUC) values. Results There were 104 study participants (35 women); median age was 56 years (interquartile range, 50-62 years). Allograft damage was found in 46 of 104 (44.2%) of participants. The median liver stiffness (8.2 kPa vs 6.3 kPa; < .01) and shear-wave dispersion slope (14.4 [m/sec]/kHz vs 10.4 [m/sec]/kHz; < .01) were higher in participants with allograft damage than in those without damage, respectively. Fibrosis stage was the only determinant factor for liver stiffness (coefficient, 1.8 kPa per fibrosis stage; 95% confidence interval: 0.1, 3.5; = .03), whereas both fibrosis stage (coefficient, 1.4 [m/sec]/kHz per fibrosis stage; 95% confidence interval: 0.3, 2.6; = .02) and necroinflammatory activity (coefficient, 1.6 [m/sec]/kHz per necroinflammatory activity grade; 95% confidence interval: 0.5, 2.7; < .01) affected shear-wave dispersion slope. The AUC for shear-wave dispersion slope in detecting allograft damage was 0.86, which was higher than that of liver stiffness (AUC, 0.75; < .01). Conclusion Shear-wave dispersion slope determined at US shear-wave elastography may help in detecting allograft damage after liver transplant. © RSNA, 2019